DIFFERENCES IN BODY COMPOSITION BETWEEN KARATE ATHLETES AND NON- ATHLETES - Željko Zombra, (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to determine the differences in the composition of the body between karate athletes and non-athletes. The research was conducted over 44 respondents, 22 karate athletes (aged 18 to 33) and 22 non-athletes (18 to 38 years old). Assessment of the body composition was based on the BIA technology, measured on the Tanita scale(model BC545N), and the variables taken into account in this measurement are age, weight,height, BMI, percentage of body fat, percentage of water, bone density, basal metabolic rate, and weight of muscle mass in kilograms and percentage. Height is measured by anthropometer per Martin. Results processing was done in the SPSS program package. For all the data collected in this study, discriptive statistics are presented, that is, the central and dispersive parameters are calculated, and the distribution normality is determined, while the differences in the variable means for assessing the composition of the body are determined by the T-test for independent samples. The results showed that a statistically significant difference exists in 6 variables: AGE (t = 3.023 with the coefficient of significance p = ,005, which is far below the theoretical limit of 0.05, the variable body weight in kilograms: TTKG (t = 2.528, with the coefficient of significance p = ,017), BMI (t = 2,994, coefficient of significance p = ,006), body fat BFAT% (t =5,352, with coefficient of significance p = ,000), variable VODA% (t = 5,948, p =, 000) and the variable the percentage value of muscle mass MISMASS% (t = 5.355 with the coefficient of significance p = ,000).